Enhanced snr-based admission control algorithm for vehicular ad-hoc network - Alwan Alrubaye, Mohammed Hasan (2020)
Vehicular Ad-hoc Network (VANET) becomes a fundamental subcategory of mobile ad-hoc networks that provides vehicles to communicate with each other and with roadside infrastructure smartly. Data traffic in VANET can be categorized into safety and non-safety, where safety is a very critical point and non-safety is related to entertainment. Various VANET performance challenges are considered in terms of Quality of Service (QoS) which cause performance degradation as performance anomaly where high rates of vehicles wait for the low rates of vehicle transmitting time and starvation problem where some vehicles cannot transfer their data. Three main achievements have been accomplished. Starting with the impact of the increasing vehicle speed on performance anomaly problem consequences has been investigated. Followed by high-speed effects on data delivery is illustrated and how 802.11p has outperformed 802.11 in terms of data delivery is also demonstrated. Lastly, starvation problem is investigated where results showed increased data loss when vehicle nodes unable to deliver data correctly. Finally, a QoS-aware Signal to Noise Ratio (SNR) admission control mechanism (QASAC) is proposed to handle the performance anomaly problem while maintaining the QoS levels for high and low traffics. This can result in wasting throughput and cause data loss. The investigation results show that 802.11p has enhanced the number of dropped packets up to 70%. Also, the 802.11p end to end delay has decreased up to 12% less than the results of the 802.11 MAC protocol. The packet delivery ratio has been enhanced by up to 41% by 802.11p. The starvation problem investigation phase shows that 802.11p perform better than 802.11 which mainly affected by the increased speed of the vehicle. QASAC assigned different SNR values to different vehicles group based on the sending SNR values and in each group. Unlike recently proposed admission control in VANET networks, the proposed architecture differentiate between both high priority and low priority traffic QASAC has been compared against the latest SNR based admission control mechanism. QASAC has enhanced the performance of data delivery up to 23% in terms of data dropping rates for high priority traffic.